The utility of superb‐microvascular imaging for evaluating the full length of carotid artery stents. Issue 4 (25th January 2019) - Hagiwara, Yuta; Shimizu, Takahiro; Hoshino, Masashi; Takao, Naoki; Araga, Takashi; Hasegawa, Yasuhiro
Abstract: Transoral carotid ultrasonography (TOCU) is a powerful tool for evaluating internal carotid artery (ICA) lesions located from the carotid bifurcation up to the level of the second cervical vertebra. Superb‐microvascular imaging (SMI) is a new Doppler imaging technique whose algorithm analyze tissue movements to minimize motion artifacts by eliminating clutter signals. SMI significantly reduces motion artifacts and allows visualization of low‐velocity blood flow even in minute vessels. TOCU with SMI produces clear intraluminal image of the distal extracranial ICA, which is not possible with conventional carotid artery ultrasonography (CUS). CUS with SMI and TOCU with SMI were performed in a patient with a history of carotid artery stenting for symptomatic left ICA stenosis, providing images of the full length of the stents with intimal hyperplasia.